Variability in the Physical and Mechanical Properties of Dendrocalamus membranaceus at Different Site Conditions at Maejo University Phrae Campus - Wanishdilokratn, Thiti; Boonyarat, Natnaruethai; Jansongsang, Nattanon; Saengkhiao, Sarita; Wangkeeree, Niracha; Wanishdilokratn, Jirapa (KKU Science Journal, 2026)
This study aimed to investigate the variation in the physical and mechanical properties of Dendrocalamus membranaceus grown in three different site conditions: forest area, area near buildings, and area near water sources within Maejo University Phrae Campus, Phrae Province. The bamboo samples were tested for physical properties, including moisture content and density, and mechanical properties, including modulus of rupture (MOR), modulus of elasticity (MOE), compressive strength parallel to grain, shear strength, and tensile strength parallel to grain, according to ASTM D143 standard testing methods. The results showed that D. membranaceus from the forest area exhibited the best performance in both physical and mechanical properties. The average values were as follows: moisture content 23.30 ± 1.19%, density 721.96 ± 6.25 kg/m³, MOR 121.92 ± 8.97 MPa, MOE 10,229.67 ± 64.82 MPa, compressive strength parallel to grain 57.70 ± 5.41 MPa, shear strength parallel to grain 7.29 ± 2.30 MPa, and tensile strength parallel to grain 181.33 ± 18.86 MPa. The findings suggest that variations in site conditions play an important role in determining the physical and mechanical properties of Dendrocalamus membranaceus.